ANALISIS PERAN BADAN PERENCANAAN PENELITIAN DAN PENGEMBANGAN DAERAH PROVINSI BENGKULU DALAM PERENCANAAN PEMBANGUNAN DI BENGKULU - Akbar, Decky Rifa’i; Rosidin, Rosidin (Yayasan Insani Mandiri Santani, 2024)
The role of the Regional Planning, Research and Development Agency of Bengkulu Province is a Regional Apparatus Organization (OPD) that plays a role as a supporting element for the government in the field of regional development planning. The purpose of this study is to find out the Role of the Regional Planning, Research and Development Agency of Bengkulu Province in Development Planning in Bengkulu whether it has run optimally in the development planning process in Bengkulu. The method used in this study is a qualitative method with a descriptive approach. The theory used in this study is the role theory from Soerjono Soekanto with indicators of active role, participatory role and passive role. The results of the study show that the implementation of the role of BAPPEDA of Bengkulu Province in development planning in Bengkulu has not fully gone well. Based on the results of observations, the researcher still found several problems in the passive role of the Bengkulu Provincial BAPPEDA that were experienced, such as differences in Central Policies (between Ministries/Institutions) related to the preparation of planning and development documents at the regional level. Second, the synergy of development planning, both at the regional and national levels, has not been optimal. The third is the difference in interests between Regencies/Cities in Bengkulu Province. Keywords: Role analysis, role of BAPPEDA